2016
DOI: 10.14710/ik.ijms.21.1.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) in water of Al-Kahlaa River in Missan Province, Iraq

Abstract: The present study was performed to have knowledge of Polycyclic Aromatic Hydrocarbons pollution status in water. The samples were collected during two seasons (winter and summer 2012 ,2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results also agreed with [13,14], about the increased lead contamination of soil and plants in the Dora region due to the rising fumes and smoke from the Dora thermal power station and the Dora refinery. The results of the study showed the analysis of water using the GC-MS device, where the results showed all aromatic hydrocarbon compounds, while some compounds appeared that exceeded the permissible limits of 10 mg L -1 , where the concentration of naphthalene compound reached 35 mg L -1 , and the compound benzo (ghi) perylene reached a concentration of 70 mg L -1 , which indicates that the river water is polluted by aromatic compounds, which are deposited and remain at the bottom of the river by the influence of sewage, station and oil facilities waste, and factory waste, and thus cause IOP Publishing doi:10.1088/1755-1315/1215/1/012038 6 cancerous diseases in humans after the transfer of these compounds from the river water to plants and animals and through the human food chain [15], and as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The results also agreed with [13,14], about the increased lead contamination of soil and plants in the Dora region due to the rising fumes and smoke from the Dora thermal power station and the Dora refinery. The results of the study showed the analysis of water using the GC-MS device, where the results showed all aromatic hydrocarbon compounds, while some compounds appeared that exceeded the permissible limits of 10 mg L -1 , where the concentration of naphthalene compound reached 35 mg L -1 , and the compound benzo (ghi) perylene reached a concentration of 70 mg L -1 , which indicates that the river water is polluted by aromatic compounds, which are deposited and remain at the bottom of the river by the influence of sewage, station and oil facilities waste, and factory waste, and thus cause IOP Publishing doi:10.1088/1755-1315/1215/1/012038 6 cancerous diseases in humans after the transfer of these compounds from the river water to plants and animals and through the human food chain [15], and as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%